2023
DOI: 10.1177/08944393231160963
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation Bias in Seeking Climate Information: Employing Relative Search Volume to Predict Partisan Climate Opinions

Abstract: In an increasingly digitized world, online information-seeking (OIS) behaviors have reflected people’s intentions and constituted a critical component in synthesizing public opinion. Climate change is among the gravest threats facing the world today, and previous studies have adopted OIS data to gauge public interest in climate change. However, such studies have ignored the psychological attributes of search keywords and the role of social identities in influencing OIS. This study explores whether search strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 104 publications
0
1
0
Order By: Relevance
“…Earlier research has shown that group members anticipate conformity to the norm of ingroup favoritism and out-group disparagement among their peers. Wang and Jaidka (2023) investigated whether search methods corresponded with the predicted confirmation biases of areas that adhere to different partisan convictions. Burgers et al (2023) concentrated on four communication biases: volume, balance, fairness and recipient engagement.…”
Section: Biasmentioning
confidence: 99%
“…Earlier research has shown that group members anticipate conformity to the norm of ingroup favoritism and out-group disparagement among their peers. Wang and Jaidka (2023) investigated whether search methods corresponded with the predicted confirmation biases of areas that adhere to different partisan convictions. Burgers et al (2023) concentrated on four communication biases: volume, balance, fairness and recipient engagement.…”
Section: Biasmentioning
confidence: 99%